Концепт и мотив: междисциплинарная соотнесенность понятий - Костина-Кассанелли, О.С. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2013)
Данная статья посвящена смысловому соотношению двух базовых понятий филологии и когнитивной лингвистики— литературного мотива и культурного концепта — и их проявлениям в современном поэтическом тексте. На основе сравнительного анализа научных понятий устанавливаются принципы их взаимодействия в практике осмысления природы современного песенного текста. Эвристичный потенциал соотнесения этих понятий показан на примерах анализа поэтических фрагментов, принадлежащих к идиолекту русского рок-поэта Б. Б. Гребенщикова. The main aim of this article is to give consideration to two basic notions of philology and cognitive linguistics, which are the motif and the cultural concept, and to their explications in modern poetry. In our research, we intended not only to fulfill a basic comparative analysis of these conceptions, but also to define at maximum the principles of possible interaction of their functions within modern song lyrics. The particularities of attraction relations between two scientific concep-tions are shown in poetical fragments belonging to Russian rock-poet B. B. Grebenshchikov’s idiolect.
Concept and motif: interdisciplinary attraction of notions
Костіна-Кассанеллі Ольга Сергіївна, аспірантка кафедри російської мови Харківського національного університету імені В. Н. Каразіна
Keywords: мотив; лейтмотив; Гребенщиков Б.Б.; рок-поэт; rock-poet; Grebenshchikov; концепт; когнитивная лингвистика; концептуализация; motif; leitmotif; concept; cognitive linguistics; conceptualization